2015
DOI: 10.3389/fpls.2015.00736
|View full text |Cite
|
Sign up to set email alerts
|

Identification, isolation, and expression analysis of heat shock transcription factors in the diploid woodland strawberry Fragaria vesca

Abstract: Heat shock transcription factors (Hsfs) are known to play dominant roles in plant responses to heat, as well as other abiotic or biotic stress stimuli. While the strawberry is an economically important fruit plant, little is known about the Hsf family in the strawberry. To explore the functions of strawberry Hsfs in abiotic and biotic stress responses, this study identified 17 Hsf genes (FvHsfs) in a wild diploid woodland strawberry (Fragaria vesca, 2n = 2x = 14) and isolated 14 of these genes. Phylogenetic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 60 publications
8
56
0
Order By: Relevance
“…These data revealed that FaTHSFA2a and FaTHSFB1a proteins were not confined in the nucleus; they can be transferred into the cytoplasm where they might conceivably perform other functions. Our results are in concordance with previous data reported by Hu et al (2015) [53]; they clearly detected most FvHSF–GFP proteins in the nucleus. However, some FvHSF–GFP proteins, including FvHSF2a, FvHSF3a, FvHSF4a, FvHSF5a, FvHSF2b, and FvHSFC1a, remained detectable in the cytosol [53].…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…These data revealed that FaTHSFA2a and FaTHSFB1a proteins were not confined in the nucleus; they can be transferred into the cytoplasm where they might conceivably perform other functions. Our results are in concordance with previous data reported by Hu et al (2015) [53]; they clearly detected most FvHSF–GFP proteins in the nucleus. However, some FvHSF–GFP proteins, including FvHSF2a, FvHSF3a, FvHSF4a, FvHSF5a, FvHSF2b, and FvHSFC1a, remained detectable in the cytosol [53].…”
Section: Resultssupporting
confidence: 94%
“…Our results are in concordance with previous data reported by Hu et al (2015) [53]; they clearly detected most FvHSF–GFP proteins in the nucleus. However, some FvHSF–GFP proteins, including FvHSF2a, FvHSF3a, FvHSF4a, FvHSF5a, FvHSF2b, and FvHSFC1a, remained detectable in the cytosol [53]. Thus, our results revealed that FaTHSFA2a and FaTHSFB1a proteins have the capability to enter the nucleus and putatively function as transcriptional regulators.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…After initially identified in yeast6, plant Hsf gene family has been identified and characterized in more and more plant species, including alfalfa ( Medicago sativa L.)21, Arabidopsis thaliana 22, rice ( Oryza sativa L.)2324, maize ( Zea mays L.)25, Medicago truncatula, Populus trichocarpa 26, wheat ( Triticum aestivum L.)27, soybean ( Glycine max )2829, Chinese cabbage ( Brassica rapa ssp. pekinensis )1030, cotton ( Gossypium hirsutum )31, pigeonpea ( Cajanus cajan ), barrel medic ( Medicago truncatula )32, pepper ( Capsicum annuum L.)3334, pear ( Pyrus bretschneideri )35, Populus euphratica 36, strawberry ( Fragaria vesca )37, tea plant ( Camellia sinensis )38, wild Chinese grapevine ( Vitis pseudoreticulata )39, etc.…”
mentioning
confidence: 99%